Impact of a probiotic-based hospital sanitation on antimicrobial resistance and HAI-associated antimicrobial consumption and costs: a multicenter study - Caselli E; Arnoldo L; Rognoni C; D'Accolti M; Soffritti I; Lanzoni L; Bisi M; Volta A; Tarricone R; Brusaferro S; Mazzacane S (Infection and Drug Resistance, 2019)
Elisabetta Caselli,1,2 Luca Arnoldo,3 Carla Rognoni,4 Maria D’Accolti,1,2 Irene Soffritti,1,2 Luca Lanzoni,2 Matteo Bisi,2 Antonella Volta,2 Rosanna Tarricone,4 Silvio Brusaferro,3 Sante Mazzacane2 1Section of Microbiology and Medical Genetics, Department of Medical Sciences, University of Ferrara, Ferrara, Italy; 2CIAS Research Interdepartmental Centre, Departments of Architecture and Medical Sciences, University of Ferrara, Ferrara, Italy; 3Department of Medicine, University of Udine, Udine, Italy; 4Centre for Research on Health and Social Care Management (CERGAS), Department of Policy Analysis and Public Management, Bocconi University, Milan, Italy Purpose: Antimicrobial resistance (AMR) is one of the major threats to human health, and the high frequency of resistant pathogens in the hospital environment can contribute to the transmission of difficult-to-treat health care-associated infections (HAIs). We recently reported that, compared with conventional chemical cleaning, the use of a microbial-based sanitation strategy (Probiotic Cleaning Hygiene System [PCHS]) was associated with remodulation of hospital microbiota and reduction of HAI incidence. Here, we aimed to analyze the impact of PCHS on AMR and related effects, such as HAI-associated antimicrobial drug consumption and costs. Patients and methods: Five Italian hospitals, enrolled in a multicenter study where conventional sanitation methods were replaced with PCHS, were included in the analysis. The study period included a 6-month observation for each sanitation type. Surface microbiota AMR was analyzed using microarray, nested PCR, antibiogram, and microdilution tests. Drug consumption data and related costs were obtained from the medical records of all hospitalized patients affected by HAIs. Results: PCHS use was associated with up to 99% decrease of the AMR genes harbored by surface hospital microbiota, independently of the resistance types originally present in each individual setting (Pc<0.01). Functional assays confirmed the molecular data, demonstrating a 33%–100% decrease of resistant strains depending on the antibiotic type. Antimicrobial drug consumption associated with HAI onset showed a global 60.3% decrease, with a 75.4% decrease of the associated costs. Conclusion: The spread of AMR in the hospital environment can be limited by the use of sanitation methods to remodulate the hospital microbiota, leading to lower antimicrobial consumption and costs. This approach might be considered as part of broader infection prevention and control strategies. Keywords: AMR, HAI, antimicrobials, drug consumption, costs